2010
DOI: 10.1371/journal.pone.0010040
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Adaptation of Staphylococcus aureus during Nasal Colonization of Humans

Abstract: The nasopharynx is the main ecological niche of the human pathogen Staphylococcus aureus. Although colonization of the nares is asymptomatic, nasal carriage is a known risk factor for endogenous staphylococcal infection. We quantified S. aureus mRNA levels in nose swabs of persistent carriers to gain insight into the regulatory adaptation of the bacterium to the nasal environment. We could elucidate a general response of the pathogen to the surrounding milieu independent of the strain background or the human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
163
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(186 citation statements)
references
References 51 publications
19
163
0
Order By: Relevance
“…The temporal expression patterns of spa have been shown to be highly strain variable, especially during post-exponential growth phases, with transcription decreasing significantly in some backgrounds while remaining much more stable in others (10). In CHE482, spa transcription increased steadily throughout exponential growth and decreased only slightly thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal expression patterns of spa have been shown to be highly strain variable, especially during post-exponential growth phases, with transcription decreasing significantly in some backgrounds while remaining much more stable in others (10). In CHE482, spa transcription increased steadily throughout exponential growth and decreased only slightly thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise roles of most of these virulence factors during colonization and pathogenesis in humans have remained largely unclear, as determination of in vivo expression of bacterial virulence factors is technically challenging. Burian et al showed by a quantitative PCR (qPCR) analysis on samples from 4 persistent nasal carriers that the adhesin genes clfB, fnbA, and isdA and the immune modulator gene chp are expressed in vivo (25). In an artificial inoculation study, clfB proved to be essential for colonization in humans (26).…”
mentioning
confidence: 99%
“…While the pathogenic roles of many S. aureus secreted factors and surface proteins have been extensively studied, the physiology of this commensal in the colonization state and other host environments has received only limited attention (12,13). Sialic acid (N-acetylneuraminic acid [Neu5Ac]) is one example of a bioavailable energy source present in many host niches (14).…”
mentioning
confidence: 99%